Identification of resection plane for anatomical liver resection using ultrasonography-guided needle insertion - Zhang, Xin; Huang, Zhenhui; Lu, Haiwu; Yang, Xuewei; Cao, Liangqi; Wen, Zilong; Zheng, Qiang; Peng, Heping; Xue, Ping; Jiang, Xiaofeng (Frontiers in Surgery, 2023)
To set up an easy-handled and precise delineation of resection plane for hepatic anatomical resection (AR).